Essential Medical Facts Every Clinician Should Know To Prevent Medical Errors, Pass Board Examinations and Provide Informed Patient Care - Taylor, Robert B.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Essential Medical Facts presents selected literature-based information clinicians need to know to provide informed patient care and avoid medical misadventures. Facts that can help make us better and safer clinicians include knowing the usefulness of palmar crease pallor in detecting anemia (not reliable), antibiotics that can cause a false positive opiate urine drug screen (fluoroquinolones), and an occasional early clue to testicular cancer (gynecomastia). Of course, keeping up to date on current medical knowledge and being curious about the implications of published research conclusions not only help assure superior clinical performance; they also bolster the preparation for board examinations. Robert B. Taylor, MD is the author and editor of more than two dozen medical books and several hundred published articles, as well a veteran of both rural private practice and chairmanship of a medical school clinical department. Essential Medical Facts is written for clinicians in all specialties, at all stages of professional life. It is a must have book for students, residents and practicing physicians, as well as nurse practitioners and physician assistants actively involved in clinical diagnosis and management of disease.
Medical facts, errors and this book -- Challenging current medical misconceptions -- Epidemiologic realities and gee-whiz facts -- Disease prevention and screening -- Risk factors and disease correlates -- Practical clinical pearls -- Laboratory testing, electrocardiography and imaging -- Alarming symptoms and red flag findings -- Therapeutic insights -- Idiosyncratic and uncommon drug effects -- Drug interactions and adventures in polypharmacy -- Alcohol, nicotine and caffeine -- Unforseen, counterintuitive and possibly prophetic findings -- Some timeless truths about medical practice.
Keywords: Medicine; Family medicine; Internal medicine; Emergency medicine; Medicine & Public Health; Medicine/Public Health, general; General Practice / Family Medicine; Internal Medicine; Primary Care Medicine